Various Recognition approach in human faces - Karthigayan, M.; Mohd Rizon, Mohamed Juhari; Sazali, Yaacob; Nagarajan, R.; Puteh, Saad; Muhammed Firdaus, Hashim; Haniza, Yazid (Universiti Teknologi Petronas (UTP), 2009)
Organized by Electrical & Electronic Engineering Programme, Universiti Teknologi PETRONAS (UTP), 1st - 3rd December 2005, Kuala Lumpur, Malaysia.